Решение одного класса задач оптимизации с нелинейными ограничениями - Лаптин, Ю.П. (Теорія оптимальних рішень, 2005)
Optimization problems are discussed which arise when complicated technical objects are modeled. Such problems contain well structured sets of nonlinear equations. Some approach is proposed for decomposition of discussed problems.